Smoki, jeże, nietoperze… Podręczny bestiariusz srebrnej biżuterii PRL-u .......... 303 - Myśliński, Michał (Fantastyczne stwory i bestie w dziejach i kulturze od antyku po czasy najnowsze, 2025)
DRAGONS, HEDGEHOGS, BATS… A HANDY BESTIARY OF SILVER JEWELLERY FROM THE POLISH PEOPLE’S REPUBLIC Research on Polish jewellery produced after 1945 (period of Polish People Republic) is a new research area in Poland in this field of applied art. One of the issues is the representation of the natural world botany and zoology, as well as mythical animals (creatures). This last iconographic sphere aroused strong interest among creators and designers, and particular attention was paid to creatures known in Polish literary and historical culture, e.g. the Wawel Dragon, the Warsaw Basilisk, etc. The remaining part of this iconographic spectrum consists of representations of exotic animals (not found in the Polish natural environment) and animals living in Poland. Analysis of the artefacts allows us to assume that such representations enjoyed considerable popularity in the 1950s and 1960s, but later the fashion for applying this type of decoration passed; currently, jewellery from the Polish People Republic period is the subject of intensive collectors’ searches.